Plexiform Fibrohistiocytic Tumor: Imaging Features and Clinical Findings - Ghuman, Marcus (Skeletal Radiol, 2018)
OBJECTIVE. To describe the imaging features of plexiform fibrohistiocytic tumor and its associated clinical findings. MATERIALS AND METHODS. An institutional database was searched to identify all patients with a pathological diagnosis of plexiform fibrohistiocytic tumor. The electronic medical record was reviewed for relevant clinical data. Radiologic images of the primary tumor site were reviewed by two radiologists to assess primary, residual, or recurrent tumor with respect to tumor location, size, morphology, MR signal characteristics and enhancement, and involvement of adjacent structures. RESULTS. Thirteen patients with imaging of the primary tumor site were identified (8 female, 5 male; mean age, 15.9 years (range, 3–41 years)). Plexiform fibrohistiocytic tumor typically manifested as a solitary, painless, firm, slow-growing lesion centered in the subcutaneous tissues, with a predilection for the upper extremity or head and neck region. Most tumors had a purely plaque-like or infiltrative morphology at MRI; some demonstrated no round or oval mass. Tumors were predominantly isointense to muscle on T1-weighted imaging and hyperintense on fluid-sensitive imaging, and enhanced after gadolinium contrast administration. Five patients (38%) had residual tumor after initial surgery, resembling postoperative changes. No patient had recurrent tumor. One patient (8%) developed metastases, to local lymph nodes and to lung. No patient died from plexiform fibrohistiocytic tumor. CONCLUSION. Plexiform fibrohistiocytic tumor often manifests as a plaque-like or infiltrative process, sometimes without a round or oval mass, most commonly in the subcutaneous tissues of the upper extremity or head and neck region. Residual tumor is often present after initial surgery, indistinguishable from postoperative changes.